The impact of alcohol consumption and physical activity on breast cancer: The role of breast cancer risk. Issue 4 (13th January 2020) - Rainey, Linda; Eriksson, Mikael; Trinh, Thang; Czene, Kamila; Broeders, Mireille J.M.; van der Waal, Daniëlle; Hall, Per
Abstract : High alcohol consumption and physical inactivity are known breast cancer risk factors. However, whether the association between these lifestyle factors and breast cancer is modified by a woman's additional breast cancer risk factors has never been studied. Therefore, a population‐based prospective cohort study of 57, 654 Swedish women aged 40–74 years, including 957 breast cancer cases, was performed. Alcohol consumption and physical activity were measured with validated web‐based self‐report questionnaires. The Tyrer–Cuzick risk prediction model was used to determine a woman's 10‐year risk of developing breast cancer. Logistic regression models were used to explore whether the effect of alcohol consumption and physical activity on breast cancer was modified by additional breast cancer risk factors. Findings showed that increased alcohol consumption was associated with a higher breast cancer risk (OR = 1.26, 95% CI 1.01, 1.59). However, the association between lifestyle factors (alcohol consumption and physical activity) and breast cancer was generally the same for women at below average, average and above average risk of developing breast cancer. Therefore, additional breast cancer risk factors do not appear to modify the association between lifestyle (alcohol consumption and physical activity) and breast cancer. Considering the general health benefits, preventative lifestyle recommendations can be formulated about alcohol consumption and physical activity for women at all levels of breast cancer risk. Abstract : What's new? Alcohol consumption and physical inactivity are known breast cancer risk factors but it is currently unclear whether all women would benefit equally from drinking less alcohol and being more physically active. The authors found no difference in association between these lifestyle factors and breast cancer in women with below average, average or above average risk of developing breast cancer. They conclude that general preventative lifestyle recommendations about alcohol intake and physical activity apply to all women regardless of their breast cancer risk.